FACTORS ASSOCIATED WITH FOOD NEOPHOBIA IN CHILDREN: SYSTEMATIC REVIEW - Thamara de Oliveira Torres; Daiene Rosa Gomes; Mússio Pirajá Mattos (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To identify the factors associated with food neophobia in children through a systematic review. Data sources: This research was based on the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The research was carried out in the PubMed, Science Direct, and Scientific Electronic Library Online databases, with the combination of health descriptors in English and Portuguese: ("Food Neophobia" OR "Feeding Behavior" OR "Food Preferences" OR "Food Selectivity") AND Child, from 2000 to 2019. Studies that evaluated factors associated with food neophobia in children were included. The quality of the studies was assessed using the Effective Public Health Practice Project: Quality Assessment Tool for Quantitative Studies (QATQS). Data synthesis: 19 studies were included in the systematic review. The prevalence of food neophobia ranged from 12.8 to 100%. The studies used three different scales to measure the level of food neophobia. The main factors associated with food neophobia were: parental influence on children's eating habits, children's innate preference for sweet and savory flavors, influence of the sensory aspect of the food, parents' pressure for the child to eat, parents' lack of encouragement and/or affection at mealtime, childhood anxiety, and diets with low variety and low nutritional quality. Conclusions: The factors associated with food neophobia permeate several areas of the child's life, thus, interprofessional follow-up becomes essential in the intervention process.